“Elaboración y aplicación de una guía de canciones infantiles para el desarrollo de lenguaje oral en los niños de segundo año de educación básica de la Unidad Educativa Fernando Daquilema, periodo 2016 - 2017” - Morocho Amboya, Myrian Elizabeth (2017)
The following research work, the main objective is the elaboration and implementation of a guide of children's songs for the development of oral language in the children of second year of basic education at "Fernando Daquilema, Educational Unit" , during the period 2016-2017 the guide of children's songs through stories and rhymes allows the student to improve their quality of attention by developing their body rhythm, relating to oral expression, expressing situations, feelings, emotions, promoting fluency, affection, spontaneity, that will support supports the vocalization. In the applied methodology is an explanatory cross-sectional survey, because it was responsible for explaining how children's songs, rhymes and songs are related to the development of oral language. We have worked with a total population of 59 boys and girls from 6 to 7 years, for the small size of the universe it was not necessary to obtain a sample. As a research instrument, the observation guide was used to obtain the required information. After obtaining the results it was identified that the students were not familiar with the use of a children's songs guide so it was necessary and timely elaborated. In conclusion, the guide was a valuable tool that allowed the development the oral language in children. It is recommended that teachers apply this guide as a tool to improve the teaching-learning process.